Middle ear osteoma: case report and literature review - Garov, E V; Zelikovich, E I; Ivoylov, A Yu; Sidorina, N G; Kaloshina, A S; Garova, E E (Vestnik otorinolaringologii, 2019)
The short literary review of frequency of occurrence, complaints, results of diagnostics and surgical treatment of patients about osteomine is presented to a drum cavity in article. Two own cases of clinical inspection and surgical treatment of patients about osteomine of a drum cavity are described.The short literary review of frequency of occurrence, complaints, results of diagnostics and surgical treatment of patients about osteomine is presented to a drum cavity in article. Two own cases of clinical inspection and surgical treatment of patients about osteomine of a drum cavity are described.